1999
DOI: 10.1007/s002449900541
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of Oscillatoria limnetica Lemmermann to Atrazine in Natural Phytoplankton Populations and in Pure Culture: Influence of Season and Temperature

Abstract: The responses of algae to herbicides depend on the sensitivity of each species, but competition within algal communities may be an important regulator of the effects of herbicides on aquatic systems. The impact of herbicides on algae also depends on abiotic factors like nutrients, light, and temperature. We examined the tolerance of the alga Oscillatoria limnetica Lemmermann to the photosystem II inhibitor herbicide atrazine under different culture conditions to assess those interactions between herbicides and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 41 publications
1
32
0
Order By: Relevance
“…Therefore, in this review, the effects of agricultural nutrient inputs will not be considered. In contrast, anthropogenic additions of hazardous compounds to waterways can significantly affect photosynthesis of aquatic organisms (DeLorenzo et al, 2001), and agrotoxics (mainly herbicides) heavily used in agricultural and industrial practices are notorious for their effects on algal and cyanobacterial physiology and growth (Bérard et al, 1999;Chalifour and Juneau, 2011). Photosynthesis-targeting herbicides, such as atrazine, simazine and terbuthylazine, act primarily on photosynthetic light reactions and inhibit carbon assimilation (Jursinic and Stemler, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in this review, the effects of agricultural nutrient inputs will not be considered. In contrast, anthropogenic additions of hazardous compounds to waterways can significantly affect photosynthesis of aquatic organisms (DeLorenzo et al, 2001), and agrotoxics (mainly herbicides) heavily used in agricultural and industrial practices are notorious for their effects on algal and cyanobacterial physiology and growth (Bérard et al, 1999;Chalifour and Juneau, 2011). Photosynthesis-targeting herbicides, such as atrazine, simazine and terbuthylazine, act primarily on photosynthetic light reactions and inhibit carbon assimilation (Jursinic and Stemler, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…But Bérard et al (1999) demonstrated that single-species tests may fail to predict indirect or system responses to toxicants, such as changes in population competition or succession.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been published about pesticide toxicity assessment on microalgae, using single species tests. However, Bérard et al (1999) demonstrated that single-species tests may fail to predict indirect or system responses to toxicants, such as changes in population competition or succession. According to these authors, studies focusing on the whole natural community provide more reliable predictions about herbicide safety in aquatic environments.…”
Section: Effects On Non-target Aquatic Plants and Algaementioning
confidence: 99%